2004
DOI: 10.1128/mmbr.68.1.109-131.2004
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic MCM Proteins: Beyond Replication Initiation

Abstract: The minichromosome maintenance (or MCM) protein family is composed of six related proteins that are conserved in all eukaryotes. They were first identified by genetic screens in yeast and subsequently analyzed in other experimental systems using molecular and biochemical methods. Early data led to the identification of MCMs as central players in the initiation of DNA replication. More recent studies have shown that MCM proteins also function in replication elongation, probably as a DNA helicase. This is consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
518
2
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(536 citation statements)
references
References 364 publications
(352 reference statements)
12
518
2
4
Order By: Relevance
“…Some studies suggested that MCM proteins could be used as a novel marker for proliferating cells (Alison et al, 2002). Based on the evidence that MCM proteins have a crucial role in regulation of cellcycle (Alison et al, 2002;Forsburg, 2004), we proposed that MCM3 proteins might represent a useful proliferative and diagnostic marker in salivary gland tumors .We analyzed MCM3 in comparison with Ki-67, in the most common benign and malignant SGTs. Our findings showed that the LI of MCM3 was significantly higher than Ki-67 LI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that MCM proteins could be used as a novel marker for proliferating cells (Alison et al, 2002). Based on the evidence that MCM proteins have a crucial role in regulation of cellcycle (Alison et al, 2002;Forsburg, 2004), we proposed that MCM3 proteins might represent a useful proliferative and diagnostic marker in salivary gland tumors .We analyzed MCM3 in comparison with Ki-67, in the most common benign and malignant SGTs. Our findings showed that the LI of MCM3 was significantly higher than Ki-67 LI.…”
Section: Discussionmentioning
confidence: 99%
“…MCM proteins which are consisted of six members, MCM2 to MCM7, interact with each other at the early stage of DNA synthesis and form a stable hetrohexamer with DNA helicase activity functioning in the DNA replication of eukaryotic cells (Forsburg, 2004;Junhui et al, 2011). Molecular evidence shows that MCM2-7 acts as a factor to ensure the genome is replicated only once in each cell cycle (Chevalier and Blow, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Our cDNA microarray result demonstrated up-regulation of SOX-4 and down-regulation of SOX-17 in ESCC, which is similar to Kormish's report and suggests that Sox-Wnt interactions may be involved in ESCC development. MCM proteins are DNA replication licensing factors and obvious markers for proliferation (Forsburg 2004). It has been reported that increased levels of MCMs marked not only proliferative malignant cells, but also precancerous cells and the potential for recurrence (Alison et al 2002;Going et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Minichromosome maintenance (MCM) proteins are conserved in eukaryotes and have essential roles in initiation and elongation during DNA replication (Tye, 1999;Labib et al, 2000;Forsburg, 2004;Pacek and Walter, 2004;Shechter et al, 2004). MCM4, -6, and -7 have been shown to unwind DNA helices in a ATP-dependent manner, whereas the heterohexameric MCM2-7 does not, suggesting that MCM4, -6, and -7 may function as the catalytic core and the replicative helicase during DNA replication (Fujita et al, 1997;Kubota et al, 1997;Labib et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…p53 also plays a critical role in G2 arrest that allows cells to avoid segregation of defective chromosomes through the regulation of many target genes during G2/M arrest (Bunz et al, 1998 to-S phase transition and also promotes dissociation of the cell division control (Cdc)2/cyclin B1 complex, inducing a G2/M arrest (Fornace et al, 1992;Vairapandi et al, 1996;Wang et al, 1999;Mak and Kultz, 2004). Minichromosome maintenance (MCM) proteins are conserved in eukaryotes and have essential roles in initiation and elongation during DNA replication (Tye, 1999;Labib et al, 2000;Forsburg, 2004;Pacek and Walter, 2004;Shechter et al, 2004). MCM4, -6, and -7 have been shown to unwind DNA helices in a ATP-dependent manner, whereas the heterohexameric MCM2-7 does not, suggesting that MCM4, -6, and -7 may function as the catalytic core and the replicative helicase during DNA replication (Fujita et al, 1997;Kubota et al, 1997;Labib et al, 2000).…”
mentioning
confidence: 99%